From Suez to Tequila : The IMF As Crisis Manager - Boughton, James (Washington, D.C. : International Monetary Fund, 1997)
The IMF was established in 1944 in part to 'give confidence' to member countries by providing short-term credits. Although the intention was that the availability of the Fund's resources should prevent countries from experiencing financial crises, in practice the institution often has found itself helping its members cope with crises after they occur. This paper examines how the role of the IMF as crisis manager has evolved over time, from its earliest loans to the exchange crisis that hit Mexico in December 1994. It argues that the defining moment for this role was the international debt crisis of 1982.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet